Synthesis of SiO2 and CaO rich calcium silicate systems via sol‐gel process: Bioactivity, biocompatibility, and drug delivery tests. Issue 9 (12th October 2013) - Catauro, M.; Papale, F.; Roviello, G.; Ferone, C.; Bollino, F.; Trifuoggi, M.; Aurilio, C.
Abstract Silica and calcium silicate amorphous materials, mixed with sodium ampicillin, a broad‐spectrum antibiotic, have been synthesized by sol‐gel method. The amorphous nature of the gels was ascertained by X‐ray diffraction analysis. The bioactivity of the synthesized materials has been put into evidence by the appearance of a crystal of hydroxyapatite on the surface of the samples soaked in a fluid simulating the composition of the human blood plasma, as detected through FTIR measurements and SEM micrographs. The present work refers to a series of in‐vitro biocompatibility tests, which has been performed on silicate and CaO rich calcium silicate gel‐glasses, to study the cell behavior when seeded on 1 cm2 material fragments, introduced into an in‐vitro culture system. 3T3 cell lines have been used and the viability has been evaluated by WST‐8 test. The composition of the adopted glasses can be expressed by the following general formula: x CaO (1 − x) SiO2 with x = 0.00; 0.30; 0.40; 0.50; 0.60. Subsequently, release kinetics in a simulate body fluid (SBF) has been investigated. The amount of sodium ampicillin released has been detected by UV‐Vis spectroscopy. The release kinetics has appeared to occur in more than one stage. All data have shown that those materials could be used as drug delivery bioactive systems. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3087–3092, 2014.